THE CLUSTERS OF TELEMEDICINE (THE SCOPE AND MAIN ECONOMIC ISSUES OF TELEMEDICINE) - Erdélyi-Madai, Réka (APSTRACT: Applied Studies in Agribusiness and Commerce, 2025)
The introduction of telemedicine tools was motivated by the need to reduce the risk of infection. This paper deals with the main areas of telemedicine. It presents a definition of telemedicine and its most typical manifestations. It discusses the role of health in economic growth. It also discusses the legislative background to telemedicine. It analyses the two major clusters of telemedicine, primary health care and VR-based care. Primary care includes online rounds, remote examinations, remote diagnostics, remote intervention, remote monitoring and surveillance. The second cluster, based on virtual reality, already includes elements such as surgical interventions, pain relief, attitude modelling, rehabilitation, anxiety and phobia management, eating disorders management, relaxation, medical care in disaster situations. A separate chapter of the study deals with the economic indicators and revenues of telemedicine. Finally, the author identifies possible areas for further research (Craig J. – Patterson V., 2005).